Plan publicitario para la empresa publicidad extrema don soto, cantón Quevedo, Año 2015. - Sotomayor Bajaña, Roberto Stalin (2015)
The overall objective of this study aims to develop an advertising plan for the company Advertising Extreme Don Soto Quevedo Canton; to achieve this objective proceeded to perform the following methodology: 1) diagnosis of the current domestic situation (in this case an interview to employees and directors of the company was held) and external (customers) of the company was conducted; 2) identification and evaluation of external and internal factors of the company Advertising Extreme Don Soto was performed; 3) Development of the proposed advertising plan strategic planning considered plan of action for the company. The study entitled "Commercial Plan for the company Advertising Extreme Don Soto Canton Quevedo" consists of the following parts: Analysis of external factors corresponding to macro factors that determine the current state of the digital national advertising, the competition factor developed in increased level of companies offering digital advertising; these forces allowed to demonstrate by analyzing the forces of Porter reality in the provision of good and service as well as pitted against its competitors. To analyze this factor we proceeded to assess, rate and evaluate external factors identifying opportunities and threats, by EFE matrix, the results are expressed in greater weight with the opportunities available to the company. Analysis of internal factors, proceeded to conduct an interview and survey to employees, management and consumers Company Advertising Extreme Don Soto. In conclusion, the advertising plan has five